Ações de sustentabilidade em laticínio de pequeno porte - Lazari, Naira Kissieli de (2023)
The dairy industry is a source of effluents, waste and atmospheric emissions that have environmental impacts. Therefore, the objective of this study was to analyze the level of sustainability of a small dairy. The basic methodology of the National Council for Clean Technologies method and the methodology of the Environmental Technical Guide for the Dairy Products Industry were used to carry out the environmental diagnosis of the production cycle and thus propose changes in the industry. Data was collected through checklists, questionnaires and technical inspections at the industry's facilities to understand its production system to carry out an environmental assessment and characterize the dairy production process to identify waste generated. After the inspections, it was possible to map the process flow and waste generated by the sectors. To understand the milk by-product, research was carried out to identify possible applications and market analysis. Based on this information, a sustainability plan was developed with proposals for improvements such as reusing whey and a monitoring plan to ensure its effective implementation.